Alternative Sigma Factor B in Bovine Mastitis-Causing Staphylococcus aureus: Characterization of Its Role in Biofilm Formation, Resistance to Hydrogen Peroxide Stress, Regulon Members - Supa-amornkul, Sirirak; Mongkolsuk, Paninee; Summpunn, Pijug; Chaiyakunvat, Pongkorn; Navaratdusit, Warisara; Jiarpinitnun, Chutima; Chaturongakul, Soraya (Frontiers in Microbiology, 2019)
Staphylococcus aureus is a major bacterial pathogen that causes subclinical bovine mastitis which can easily developed into a chronic case. The alternative sigma factor B (σB) has been shown to be a global regulator for S. aureus infection. In this study, the role of σB was explored in a mastitis-causing S. aureus strain RF122. A sigB null (ΔsigB) mutant was constructed and analyzed for its phenotypes and transcriptome in comparison to those of the wild type strain. Our study found that σB is essential for biofilm formation as sigB mutant strain produced biofilm significantly less than that of the wild type at 48 h. σB is involved in response to H2O2 stress. However, σB plays a minor or no role in resistance to antiseptics (e.g., povidone-iodine and chlorhexidine), resistance to tested antibiotics, hemolysin activity, and invasion ability. RNA sequencing identified 225 σB-dependent genes, of which 171 genes are positively regulated and 54 genes are negatively regulated. The identified genes are involved in stress response, pathogenesis, and metabolic mechanism. Quantitative TaqMan RT-PCR was performed to verify the RNA-sequencing results i.e., σB is a positive regulator for asp23, sarA, katA, yabJ, sodA, SAB2006c, and nrdD expressions. In RF122 strain, σB plays a role in biofilm formation, general stress response (e.g. H2O2), and regulation of virulence factor and virulence-associated genes.